Retigabine, a Kv7.2/Kv7.3-Channel Opener, Attenuates Drug-Induced Seizures in Knock-In Mice Harboring Kcnq2 Mutations - Ihara, Yukiko; Tomonoh, Yuko; Deshimaru, Masanobu; Zhang, Bo; Uchida, Taku; Ishii, Atsushi; Hirose, Shinichi (PloS one, 2016)
The hetero-tetrameric voltage-gated potassium channel Kv7.2/Kv7.3, which is encoded by KCNQ2 and KCNQ3, plays an important role in limiting network excitability in the neonatal brain. Kv7.2/Kv7.3 dysfunction resulting from KCNQ2 mutations predominantly causes self-limited or benign epilepsy in neonates, but also causes early onset epileptic encephalopathy. Retigabine (RTG), a Kv7.2/ Kv7.3-channel opener, seems to be a rational antiepileptic drug for epilepsies caused by KCNQ2 mutations. We therefore evaluated the effects of RTG on seizures in two strains of knock-in mice harboring different Kcnq2 mutations, in comparison to the effects of phenobarbital (PB), which is the first-line antiepileptic drug for seizures in neonates. The subjects were heterozygous knock-in mice (Kcnq2Y284C/+ and Kcnq2A306T/+) bearing the Y284C or A306T Kcnq2 mutation, respectively, and their wild-type (WT) littermates, at 63-100 days of age. Seizures induced by intraperitoneal injection of kainic acid (KA, 12mg/kg) were recorded using a video-electroencephalography (EEG) monitoring system. Effects of RTG on KA-induced seizures of both strains of knock-in mice were assessed using seizure scores from a modified Racine's scale and compared with those of PB. The number and total duration of spike bursts on EEG and behaviors monitored by video recording were also used to evaluate the effects of RTG and PB. Both Kcnq2Y284C/+ and Kcnq2A306T/+ mice showed significantly more KA-induced seizures than WT mice. RTG significantly attenuated KA-induced seizure activities in both Kcnq2Y284C/+ and Kcnq2A306T/+ mice, and more markedly than PB. This is the first reported evidence of RTG ameliorating KA-induced seizures in knock-in mice bearing mutations of Kcnq2, with more marked effects than those observed with PB. RTG or other Kv7.2-channel openers may be considered as first-line antiepileptic treatments for epilepsies resulting from KCNQ2 mutations.